Deceptive geometries: Spatial analysis and design through the study of visual illusions - Jonsson, Daniel (My University, 2022)
Not everything is as it seems. Our perception of our surroundings, and consequently our understanding of reality, is merely a product of our own interpretation. Our eyes only receive two-dimensional projections of the three-dimensional world, which our brains then combine and reinterpret as something three-dimensional. Therefore, our perception can also easily be deceived. This has been used by architects throughout history, either to create amazement or to enhance certain architectonic features. Deceptive Geometries is an umbrella term, coined by the author, for all geometries that in some way feel unintuitive or deceive your perception of reality. This thesis aims to define by example what such geometries can be, and investigate how they can be integrated in architectural design to choreograph spatial experiences. The conventional way of representing a building with orthographic projections, i.e. plan and façade drawings, is convenient for describing the geometry in a compact manner. However, it does not reflect how the building is perceived in reality. For architecture in general, and geometric visual illusions in particular, the relation between subject and object plays a central role to the experience, as the vantage point of the observer is crucial to the perception of space. Thus, an extension to descriptive geometry is developed, with the purpose to capture the perceived geometry in a progression through space, and to decipher visual illusions. The thesis consists of an exploration of deceptive geometries and related phenomena, followed by the development of a representation method. The two parts are then synthesized into a speculative design proposal for a building located by the Three-Country Cairn, where the borders of Sweden, Norway and Finland meet. Here, a symbolic representation of the tripoint is created, serving as a testbed for integrating deceptive geometries in architecture. The overall hope is to contribute to a raised awareness of the importance of geometry to how we understand space, and how easily our perception can be manipulated. Because not everything is as it seems.
Keywords: Visual illusions; Impossible objects; Architectural representation; Descriptive geometry